1995
DOI: 10.1002/ajmg.1320550415
|View full text |Cite
|
Sign up to set email alerts
|

Tooth agenesis in down syndrome

Abstract: We studied the frequency and pattern of tooth agenesis in a Danish population with Down syndrome, trisomy 21 (46 females and 54 males). The control group consisted of a normal Danish population (2424 females and 2431 males) [Rølling, 1980: Scand J Dent Res 88:365-369; Ravn and Nielsen, 1973: Tandlaaegebladet 77:12-22]. We found that individuals with Down syndrome have an occurrence of agenesis that is some 10 times greater that in the general population with a higher frequency in males than in females. Agenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 24 publications
5
42
0
2
Order By: Relevance
“…Most studies report that mandibular second premolars, maxillary lateral incisors, maxillary second premolars, and mandibular central incisors are the teeth most often affected (in decreasing order). 35 In DS, the prevalence of hypodontia is much greater and more severe [12][13][14][15][16][17][18][19][20][21][22] and is recognized as a characteristic phenotypical feature of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies report that mandibular second premolars, maxillary lateral incisors, maxillary second premolars, and mandibular central incisors are the teeth most often affected (in decreasing order). 35 In DS, the prevalence of hypodontia is much greater and more severe [12][13][14][15][16][17][18][19][20][21][22] and is recognized as a characteristic phenotypical feature of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…38 In DS, it has been hypothesized that altered peripheral nervous system growth and abnormal development of localized chondral elements 16 may contribute as potential mechanisms responsible for the greater occurrence of dental agenesis. A recent report described that trigeminal nerve fiber growth and patterning are integrated with tooth morphogenesis, and the report hypothesized that mesenchymal dental follicles fail to form as a result of inadequate local epithelial-mesenchymal interactions due to thyroid deficiency, causing delayed proliferation of nerve cells and decreased rate of neuron production in DS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Japanese (Kumasaka et al, 1997) and Brazilian studies (Acerbi et al, 2001), found 60-63% of DS individuals had one or more missing teeth. In a detailed study, Russell and Kjaer (1995) studied 100 DS individuals and compared with Danish normal population. Missing teeth had a 10 times greater frequency in DS individuals than in general population and a higher frequency in males than in females.…”
Section: Hypodontiamentioning
confidence: 99%